PENYELEWENGAN NILAI-NILAI PANCASILA - Maulida Arsya Askori; Naina Sonia (Eastasouth Institute, 2023)
The lack of public awareness in terms of misappropriation of Pancasila values ​​in people's lives makes Pancasila ideology sidelined. Deviations against Pancasila values ​​still occur frequently in state life and do not reflect attitudes that are in accordance with Pancasila. The purpose of this research is to provide knowledge and information to the public that the deviation of Pancasila values ​​in our lives is so diverse and we often do it accidentally or deliberately. Pancasila values ​​and the need to provide information about the misappropriation of Pancasila values ​​through Pancasila Education courses. The results of this study indicate that any misappropriation of Pancasila values ​​has not been properly realized, as seen from a number of cases that have occurred in Indonesia in recent years which illustrate an imbalance between Pancasila values ​​and this is a special concern of the government.